Reference Values for Wristband Accelerometry Data in Children Aged 6–11 Years of Age - Lammers, Astrid E.; Romanowski, Anna Lena; Baumgartner, Helmut; Diller, Gerhard-Paul; Uebing, Anselm (Frontiers in Pediatrics, 2022)
Objectives: Wristband activity trackers (accelerometers) could serve as a convenient monitoring tool to continuously quantify physical activity throughout the day. We aim to provide reference values for the use of these devices in healthy children. Methods: Children were recruited at a local school and provided with activity trackers (Fitbit Charge 2). Pupils were instructed to wear devices during all normal daytime activities over a period of 11-15 days. Demographic data, total number of daily steps and heart rate were recorded. In addition, all children/parents were asked to complete a questionnaire providing information about daily physical routine (mode of transport to school, sporting activities as well as sport club memberships). Results: 302 children (54.6% boys; median age 8.7 years) participated in this prospective study. Median wearing time of the device was 12.1 hours/day. Overall, the median daily total step count was 12,095. Median step counts/day were significantly higher in boys compared to girls (13,015 vs. 11,305 steps/day; p<0.0001). In addition, step counts were significantly higher during the week, compared to weekend days. The effect of age on daily step count was found to be non-linear: The total daily step count increased from 6 to 8.5 years of age, while older children (aged >8.5 years) had lower step counts compared to the younger children. Significant predictors of the daily step count were male gender (+1,324.9 steps, p=0.0008), mode of transportation to school (walking, bicycle, scooter: +865.5 steps p=0.049), active membership in a sports club (+1,324.9 steps/day, p=0.0008), and number of structured units of physical exercise performed (+336.5/per 45 minutes, p<0,0001). Severe obesity was associated with a significant reduction in total daily step count. (-3,037.7 steps/day, p=0.015) Conclusion: Our prospective cohort study of healthy school children provides reference values for wristband accelerometers in normal individuals. In addition, it clarifies the effect of age, body weight and lifestyle on normal daily step counts in school children. This data should be helpful to judge the degree of physical limitation of patients compared to healthy peers.